Treatment of Citrate Accumulation Using Continuous «CalciumFree» Hemodiafiltration in a Patient with Acute Kidney Injury Undergoing Cardiac Surgery - S. V. Kolesnikov; A. S. Borisov; V. V. Lomivorotov (Общая реаниматология)
Regional citrate anticoagulation (RCA) is an increasingly common technique at continuous renal replacement therapy in critically ill patients with acute kidney injury (AKI). Regardless of the new anticoagulation protocols of RCA, citrate accumulation is remaining infrequent but unfavorable complication with poor outcome. Traditional treatment of this complication includes interruption of citrate administration, as well as increasing theflow of blood and dialysate.Objective: to evaluate safety and effects of a new modality, the continuous «calciumfree» hemodiafiltration, on electrolyte and acidbase status in a patient undergoing cardiac surgery with citrate accumulation after RCACRRT.Materials and metods. Reduced level of calcium in the extracorporeal circuit has been achieved by applying calciumfree CiCa Dialysate K4 solution for predilution and dialysate. To prevent hypophosphatemia and hypomagne semia 500 ml/h Multiplus K+ solution was administered in a postdilution mode. Desired level (0.91.2 mmol/L) of ionized calcium was achieved by continuous infusion of 5% calcium chloride 612 ml/h into a separate central vein line. Results. Although the target level (0.5mmol/l) of calcium after hemofilter was achieved only after 16 hours, the lifespan of the extracorporeal circuit was 23.5 hours. Total serum calcium decreased from 3.27 to 1.98 mmol/L. Other markers of acidbase balance had been fully normalized.Conclusion. «Calciumfree» hemodiafiltration might be a promising treatment option for a citrate accumulation syndrome that ensures citrate removal and establishes satisfactory anticoagulation.